Both male and female meiosis contribute to non‐Mendelian inheritance of parental chromosomes in interspecific plant hybrids (Lolium × Festuca). Issue 2 (9th February 2023) - Majka, Joanna; Glombik, Marek; Doležalová, Alžběta; Kneřová, Jana; Ferreira, Marco Tulio Mendes; Zwierzykowski, Zbigniew; Duchoslav, Martin; Studer, Bruno; Doležel, Jaroslav; Bartoš, Jan; Kopecký, David
Summary: Some interspecific plant hybrids show unequal transmission of chromosomes from parental genomes to the successive generations. It has been suggested that this is due to a differential behavior of parental chromosomes during meiosis. However, underlying mechanism is unknown. We analyzed chromosome composition of the F2 generation of Festuca  ×  Lolium hybrids and reciprocal backcrosses to elucidate effects of male and female meiosis on the shift in parental genome composition. We studied male meiosis, including the attachment of chromosomes to the karyokinetic spindle and gene expression profiling of the kinetochore genes. We found that Lolium and Festuca homoeologues were transmitted differently to the F2 generation. Female meiosis led to the replacement of Festuca chromosomes by their Lolium counterparts. In male meiosis, Festuca univalents were attached less frequently to microtubules than Lolium univalents, lagged in divisions and formed micronuclei, which were subsequently eliminated. Genome sequence analysis revealed a number of non‐synonymous mutations between copies of the kinetochore genes from Festuca and Lolium genomes. Furthermore, we found that outer kinetochore proteins NDC80 and NNF1 were exclusively expressed from the Lolium allele. We hypothesize that silencing of Festuca alleles results in improper attachment of Festuca chromosomes to karyokinetic spindle and subsequently their gradual elimination.